TAXONOMIC REVIEW OF CHONDRITES AFFINIS (STERNBERG, 1833) FROM CRETACEOUS-NEOGENE OFFSHORE-DEEP-SEA TETHYAN SEDIMENTS AND RECOMMENDATION FOR ITS FURTHER USE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The branched trace fossil Chondrites affinis (Sternberg, 1833), synonymised so far with C. targionii (Brongniart, 1828), has been analyzed in an exceptionally well preserved specimen from the Saraceno Formation (?Upper Cretaceous; ?Eocene-Miocene) in the southern Italy, its holotype (Prague Museum), and in other materials. It appeared that C. affinis displays a smaller burrow system/burrow width ratio and a larger size (burrow width typically over 4 mm and burrow system width over 150 mm) than C. targionii, without continuity of the latter parameters between these ichnospecies. Therefore, Chondrites affinis is considered as a separate ichnospecies, and is recommended for further use. It occurs in Upper Cretaceous to Neogene offshore, deep-sea, mostly marly sediments, and its unquestionable occurrences are known so far from the European Alpides.
Keywords: Ichnology; Ichnotaxonomy; Chondrites; Offshore-deep-sea sediments; Cretaceous; Italy